Application of Al-Doped SiC High Emissivity Powder Material Based on Infrared Radiating Coating - Liu, Jun; Li, Yong; Li, Jiangtao (Asian Journal of Chemistry, 2014)
Combustion synthesis technology was used to prepare an Al-doped SiC infrared radiating ceramic powder material. The material’s microstructure was analyzed by XRD, TEM and an IRE-2 infrared emitting ability survey meter. The relationship between the powder’s architectural feature and the infrared radiating performance was obtained. According to the results, the Al atom enters the intracell by replacing a silicon atom and forms a structure of finite replacement-type solid solution, which results in an expansion of the SiC lattice parameter that consequently forms multiple structural defects, distorts the lattice and improves the emissivity. Furthermore, we found that the powder’s normal emissivity in the scope of 8-12 μm can reach 0.99. Finally, the powder’s application to infrared heating coating is discussed.